2000
DOI: 10.1097/00006199-200005000-00002
|View full text |Cite
|
Sign up to set email alerts
|

An Explanatory Model of Health Promotion and Quality of Life in Chronic Disabling Conditions

Abstract: The final model supports the hypothesis that quality of life is the outcome of a complex interplay among contextual factors (severity of illness), antecedent variables (Stuifbergen & Rogers, 1997), and health-promoting behaviors. The strength of direct and indirect paths suggests that interventions to enhance social support, decrease barriers, and increase specific self-efficacy for health behaviors would result in improved health-promoting behaviors and quality of life. Further research using a longitudinal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
179
1
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(200 citation statements)
references
References 17 publications
11
179
1
9
Order By: Relevance
“…The CESD-10 has demonstrated good reliability and validity with various populations, including people with chronic and disabling conditions. 21,22 For this study, the Cronbach α coefficient of the CESD-10 was 0.85.…”
Section: Data-analysis Planmentioning
confidence: 66%
“…The CESD-10 has demonstrated good reliability and validity with various populations, including people with chronic and disabling conditions. 21,22 For this study, the Cronbach α coefficient of the CESD-10 was 0.85.…”
Section: Data-analysis Planmentioning
confidence: 66%
“…Literature shows that a low level of illness acceptance may worsen one's health condition and increase disease progression [34,35]. In contrast, higher disease acceptance enhances one's motivation to improve one's wellbeing [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…For three others this was their first contribution as a patient research partner, although they had attended a training day in preparation. The partners were sent a booklet containing visual analogue scales (VAS) or NRS found in the literature review [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 3) selected by the research team, or items or subscales from questionnaires where no VAS/NRS could be identified that assessed a similar notion in to that in the original interview data [15]. Not all scales or items identified in the literature were included.…”
Section: Identification Of Instruments To Measure Priority Outcomes (mentioning
confidence: 99%